Direct Access to Substituted 4-CF3 β-Lactams at the C-3 Position - Skibińska, Monika; Kaźmierczak, Marcin; Milcent, Thierry; Cytlak, Tomasz; Koroniak, Henryk; Crousse, Benoit (Frontiers in Chemistry, 2019)
Mono and disubstituted 4-CF3 β-lactams at the C-3 position have been obtained stereoselectively under basic conditions. Wide range of function such as alcohol, alkyls, aryls, ester, double and triple bonds have been introduced.